Ekonomiczne skutki wprowadzenia ustawy o działalności leczniczej - Łagowski, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The Act on Medical Activity is a move in the right direction, but without concurrent comprehensive changes to the shape of the entire system it is incomplete. The legislature did not avoid imperfections, despite the fact that the project was prepared in a quiet mode, without haste and without clear temporary order, as it usually happens. Thirty months after the Act was passed, medical services market observers suggest amendments and introduction of new regulations to the Act. However, the authorities do not seem to hear these comments and criticism.
Keywords: ekonomia ochrony zdrowia; polityka ochrony zdrowia